One algebraic method to study stability of linear normal systems in partial derivatives - Zhestkov , S. V.; Ermolaev , E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
In certain special classes of linear normal systems of partial differential equations, sufficient conditions for the trivial solution of the Cauchy problem to be stable can be phrased in terms of the coefficients. The determination of such classes is based on a modified method of majorants, combined with the use of n-dimensional hypercomplex numbers with associative-commutative multiplication.